الفروق الفردية في حل المشكلات الهندسية بين تلاميذ المرحلة الإعدادية مرتفعي ومنخفضي العبء المعرفي - عبدالله، سيد محمد جابر Abdullah, Sayed Mohammed Jaber; حسن، سيد محمدي صميدة; هلال، محمد إبراهيم جودة Helal, Mohammed Ibrahim Jawdah; حرب، سامح حسن سعد الدين (جامعة بنها - كلية التربية, 2022)
هدفت الدراسة إلى الكشف عن الفروق في حل المشكلات الهندسية بين مرتفعي ومنخفضي العبء المعرفي (الخارجي، والداخلي، ووثيق الصلة) لدى عينة تكونت في صورتها النهائية من (92) تلميذ وتلميذة من تلاميذ الصف الثالث الإعدادي بمدرستي كفر منصور الإعدادية المشتركة وكفر كردي الإعدادية المشتركة التابعتين لإدارة كفر شكر التعليمية التابعة لمديرية بنها بمحافظة القليوبية، بالفصل الدراسي الثاني للعام الدراسي (2020-2021م)، وقد تم توزيع العينة- وفقا لدرجاتهم على كل بعد على حدة من أبعاد مقياس العبء المعرفي (إعداد: الباحث)- إلى مجموعتين هما: مرتفعي العبء المعرفي (الخارجي، والداخلي، ووثيق الصلة)، ومنخفضي العبء المعرفي (الخارجي، والداخلي، ووثيق الصلة)، وتم تطبيق اختبار حل المشكلات الهندسية، وتوصلت الدراسة إلى النتائج التالية: - توجد فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات تلاميذ المرحلة الإعدادية مرتفعي ومنخفضي العبء المعرفي الخارجي في حل المشكلات الهندسية لصالح منخفضي العبء المعرفي الخارجي. - توجد فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات تلاميذ المرحلة الإعدادية مرتفعي ومنخفضي العبء المعرفي الداخلي في حل المشكلات الهندسية لصالح منخفضي العبء المعرفي الداخلي. - وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات تلاميذ المرحلة الإعدادية مرتفعي ومنخفضي العبء المعرفي وثيق الصلة في حل المشكلات الهندسية لصالح مرتفعي العبء المعرفي وثيق الصلة. The study aimed to reveal the differences in solving Geometry problems between the high and low cognitive load (extraneous, intrinsic, and germane) of (92) male and female preparatory stage pupils at the third-grade. The study sample was pupils at Kafr Mansour preparatory school and Kafr Kurdie preparatory school, that were assigned to of Kafr Shukr educational administration affiliated to the Benha Directorate in Qaliubiya Governorate, in the second semester of the academic year (2020-2021) . The sample was distributed in each dimension of the cognitive load scale that was prepared by the current study researcher into two groups: the first group was the high cognitive load pupils (extraneous, intrinsic, and germane) and the second group was the low cognitive load pupils (extraneous, intrinsic, and germane); and the geometry problem solving test was applied, and the study concluded the following results: -There are statistically significant differences at the level of (0.01) between the mean scores of the high and low extraneous cognitive load pupils of the preparatory stage in solving geometry problems in favor of the low extraneous cognitive load. -There are statistically significant differences at the level of (0.01) between the mean scores of the high and low intrinsic cognitive load pupils of the preparatory stage in solving geometry problems in favor of the low intrinsic cognitive load. -There are statistically significant differences at the level of (0.01) between the mean scores of the high and low germane cognitive load pupils of the preparatory stage in solving geometry problems in favor of the high germane cognitive load.
Keywords: الأهداف التربوية -- تنمية المهارات -- العبء المعرفي -- طلبة المرحلة الإعدادية